Using power as a metric to quantify vibration transmitted to the cyclist - Pelland-Leblanc, J.-P.; Lépine, J.; Champoux, Y.; Drouet, J.-M. (Procedia Engineering, 2014)
For the purposes of new product development, the cycling industry requires an objective means of ranking bicycle comfort with regard to vibration response. Acceleration is currently the standard metric used in the industry. Absorbed power and transmitted force have recently been proposed as metrics to quantify bicycle comfort. The objective of this paper is to compare the relative merits of these 3 metrics. Measurements were done while comparing 2 bikes tested on a cobblestone road and on a laboratory simulator. Acceleration and absorbed power give the same anticipated results but the absorbed power has several advantages over the other metrics.